Magi : the labyrinth of magic. 24 - Otaka, Shinobu (VIZ Media, 2017)
"The saga of the lost world of Alma Tran continues. Solomon readies for a final battle against his father David, but the fate of the world may already be set. Solomon and his comrades confront the ultimate power in their universe in a bid to prevent the apocalypse. And as everything begins to fall apart, Ugo puts a desperate plan in motion if this world cannot be saved, perhaps there can be hope for the next"--pg.4 of cover.